2015
DOI: 10.1093/jrr/rrv066
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of damage due to low-dose radiation exposure in mice: construction and application of a biodosimetric model using mRNA indicators in circulating white blood cells

Abstract: Biodosimetry, the measurement of radiation damage in a biologic sample, is a reliable tool for increasing the accuracy of dose estimation. Although established chromosome analyses are suitable for estimating the absorbed dose after high-dose irradiation, biodosimetric methodology to measure damage following low-dose exposure is underdeveloped. RNA analysis of circulating blood containing radiation-sensitive cells is a candidate biodosimetry method. Here we quantified RNA from a small amount of blood isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Recently, gene expression changes have been recognized as radiation exposure markers [ 18 , 19 ]. These marker genes include cell cycle-related Ccng1, Cdk1na, apoptosis-related Bax, and Fas genes [ 23 , 24 , 25 ]. Many gene expression studies have focused on developing bio-dosimetry methods using peripheral blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, gene expression changes have been recognized as radiation exposure markers [ 18 , 19 ]. These marker genes include cell cycle-related Ccng1, Cdk1na, apoptosis-related Bax, and Fas genes [ 23 , 24 , 25 ]. Many gene expression studies have focused on developing bio-dosimetry methods using peripheral blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the deglycosylation of this protein cannot be used as a marker to evaluate the effect of radiation doses received by individuals such as astronauts or persons exposed to the Fukushima Dai-ichi nuclear power plant disaster of 2011. Certain candidate biomarkers are evaluated based on altered expression of specific mRNAs after exposure of cells to low-dose radiation [ 27 , 28 ]. This idea must be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Collective analysis of peripheral blood cells is useful due to its availability. In an analysis of whole white blood cells, exposure to LDR < 0.5 Gy resulted in increased expression of DNA damage-inducible genes ( Ishihara et al, 2016 ). In particular, it was found that the expression of Ku70, Ku80, and H2A histone family member X (H2AX) – but not that of γH2AX – was induced in peripheral blood cells upon prolonged LDR exposure in a rat model ( Zhang et al, 2016b ).…”
Section: The Organ-specific Effects Of Ldr In Cell and Mouse Modelsmentioning
confidence: 99%